Flood Hazard Assessment and Vulnerability Analysis in Garyllis River Basin, Cyprus - Kountouri, Josefina; Panagiotou, Constantinos F.; Tsouni, Alexia; Sigourou, Stavroula; Pagana, Vasiliki; Loulli, Eleni; Evagorou, Evagoras S.; Mettas, Christodoulos; Kontoes, Charalampos; Hadjimitsis, Diofantos G. (My University, 2024)
Flood is defined as one of the most devastating natural hazards that lead to immeasurable damages in terms of human settlements and economic losses. As part of the Mediterranean region, Cyprus suffers from this disaster, being subjected to extreme events, land use changes and economic development. In this study, flood hazard is estimated and its extent on residential areas, villages, and agricultural areas located within the Garyllis basin is mapped and analyzed with the integration of remote sensing techniques, GIS, in-situ data, field visits and hydraulic modeling. Open-source HEC-RAS software has been used to estimate the spatial pattern of water surface depths during a 24-hour event for a 1000-year return period. Preliminary results indicate that the areas most susceptible to flooding are observed at the southern part of the basin. The intent is to assist policy makers and planners in the development of flood mitigation measures.
Keywords: Garyllis river; Flood risk assessment; flood extent; vulnerability; mitigation measures